Development of Process Technology for Preparation of Ready-to-eat Puffed Potato Cubes - Singh, K K; Sahay, K M; Dange, Mohini M; Patel, S (Journal of Agricultural Engineering, 2007)
Potato chips are very popular snack food in India and the French fries are also getting popularity in big cities of the country. But potato chips and French fries both contain high amount of fat 36.8 to 38.1% respectively, which is harmful for human health. Therefore, the need was realized to develop puffed potato cubes that could be used as oil free snack food. The puffing parameters: temperature, time, cube size, and moisture content were studied with respect to volume expansion ratio and non enzymatic browning of the puffed cubes. The best conditions observed were puffing temperature of 150degree C, puffing time of 4 min., cube size of 12 mm, and moisture content of 50% w.b. At these conditions, volume expansion ratio of 1.6 and optical density of 0.2 were observed. The freshly puffed cubes were very much liked by the panelists and its acceptance was at par with French fries. A puffing machine was developed to process 5 kg puffed potato cubes per hour.